Forgotten but not gone: Yersinia infections in England, 1975 to 2020 - Šumilo, Dana; Love, Nicola K; Manuel, Rohini; Dabke, Girija; Paranthaman, Karthik; Jenkins, Claire; McCarthy, Noel D (Euro surveillance : bulletin européen sur les maladies transmissibles, 2023)
BackgroundYersiniosis is one of the most common food-borne zoonoses in Europe, but there are large variations in the reported incidence between different countries.AimWe aimed to describe the trends and epidemiology of laboratory-confirmed infections in England and estimate the average annual number of undiagnosed cases, accounting for under-ascertainment.MethodsWe analysed national surveillance data on cases reported by laboratories in England between 1975 and 2020 and enhanced surveillance questionnaires from patients diagnosed in a laboratory that has implemented routine testing of diarrhoeic samples since 2016.ResultsThe highest incidence of infections in England (1.4 cases per 100,000 population) was recorded in 1988 and 1989, with being the predominant species. The reported incidence of infections declined during the 1990s and remained low until 2016. Following introduction of commercial PCR at a single laboratory in the South East, the annual incidence increased markedly (13.6 cases per 100,000 population in the catchment area between 2017 and 2020). There were notable changes in age and seasonal distribution of cases over time. The majority of infections were not linked to foreign travel and one in five patients was admitted to hospital. We estimate that around 7,500 infections may be undiagnosed in England annually.ConclusionsFindings suggest a considerable number of undiagnosed yersiniosis cases in England, with possibly important changes in the epidemiology. The apparently low incidence of yersiniosis in England is probably due to limited laboratory testing.